Dietary Luffa cylindrica (L.) Roem promotes branched-chain amino acid catabolism in the circulation system via gut microbiota in diet-induced obese mice. (1st August 2020) - Zhang, Lu; Yue, Yunshuang; Shi, Mengxuan; Tian, Meiling; Ji, Junfu; Liao, Xiaojun; Hu, Xiaosong; Chen, Fang
Highlights: BCAAs can be regarded as serum biomarkers for obesity. Luffa potentially suppressed bacterial BCAA biosynthesis. Luffa -affected bacterial metabolites triggered tissue-specific BCAA catabolism. Luffa improved circulating BCAA dysfunction via gut microbiota to attenuate obesity. Abstract: High circulating branched-chain amino acid (BCAA) levels can be diagnosis indicators for obesity. Luffa cylindrica ( luffa ) is one of vegetables against obesity. However, whether the anti-obesity of luffa is associated with BCAA metabolism and gut microbiota remains unknown. Here, we used conventionally raised diet-induced obese (DIO) mice to prove dietary luffa could reduce higher circulating BCAA levels and upregulate the tissue-specific expressions of BCAA-catabolizing enzymes. Meanwhile, dietary luffa selectively decreased the relative abundances of g_Enterortabdus, g_Eubacterium_xylanophilum_group and g_Butyricicoccus that exhibited significantly positive correlations with BCAA levels, BMI and HOMA-IR. Bacterial functionality prediction indicated dietary luffa potentially inhibited bacterial BCAA biosynthesis for reducing BCAAs supplementation. More importantly, dietary luffa had no impacts on BCAA catabolism in germ-free-mimic DIO mice. Thus, dietary luffa improved BCAA dysfunction via gut microbiota to attenuate obesity. This study offers a novel insight into dietary intervention against obesity from the aspect of gut microbiota-amino acid metabolism.